Transvaginal Sonographic Evaluation of Adenomyosis, Leiomyoma or Combined Adenomyosis and Leiomyoma: Association with Histopathological Outcomes - T, Hossain; M, Begum; A, Kabir; A, Mahbub; A, Hossain; T, Sultana; F, Nazlee (Archives of Clinical and Biomedical Research, 2025)
This prospective study was conducted in the Department of Histopathology and Radiology and Imaging of the Islami Bank Hospital, Mirpur and the Department of Radiology and Imaging, BSMMU Dhaka to evaluate the accuracy, sensitivity, specificity, positive and negative predictive value (PPV& NPV) for the diagnosis of adenomyosis, leiomyoma, or combined adenomyosis and leiomyoma by the use of transvaginal ultrasonography (TVS) compared to the histopathological findings. Transvaginal sonography is a popular method to diagnose adenomyosis, leiomyoma or combined adenomyosis and leiomyoma which ultimately lead to hysterectomy followed by histopathology. One hundred patients were scheduled for hysterectomy after preoperative transvaginal sonography. All sonographic findings were compared with the histopathological results.The symptomatic patients were diagnosed as adenomyosis, leiomyoma or both by transvaginal ultrasound (TVS) technique. These diagnosed patients routinely underwent hysterectomy or myomectomy with excision of surrounding myometrium. Following surgery, histopathology of hysterectomy or myomectomy specimens were done by the experienced pathologists. TVS diagnosis of adenomyosis was sensitive but not highly specific. TVS was more sensitive, specific and accurate in the diagnosis of leiomyoma or combined adenomyosis and leiomyoma. Our study suggests that TVS is a very valuable noninvasive method that can be utilized in the diagnosis of leiomyoma or combined adenomyosis and leiomyoma. TVS is sensitive but not specific in the diagnosis of adenomyosis only. This study also suggests that histopathology werethe ‘gold standard’ for the diagnosis of adenomyosis, leiomyoma or combined adenomyosis and leiomyomabased on the accuracy, sensitivity, specificity, positive and negative predictive value (PPV& NPV). It is evident that there is a strong association between transvaginal sonographic evaluation of adenomyosis, leiomyoma or their combination with histopathological findings (p<0.05).